A Pair of Chromone Epimers and an Acetophenone Glucoside from the Mangrove Endophytic Fungus Mycosphaerella sp. L3A1. Issue 12 (17th November 2022) - Tan, Qi; Yang, Wencong; Zhu, Ge; Chen, Tao; Wu, Jun; Zhu, Yujia; Wang, Bo; Yuan, Jie; She, Zhigang
Abstract: Three new compounds, including a pair of chromone derivatives (1 –2 ), and an acetophenone glucoside (3 ), together with three known compounds (4 –6 ), were isolated from the mangrove endophytic fungus Mycosphaerella sp. L3A1. Their structures were elucidated by HR‐ESI‐MS analysis and extensive spectroscopic data. The absolute configurations of new compounds were determined using single‐crystal X‐ray diffraction analysis, electronic circular dichroism (ECD) calculations and chemical hydrolysis. In bioassays, compound 4 showed moderate cytotoxic activity against MDA‐MB‐435, HCT116, and SNB19 with IC50 values in the range of 18.5‐26.29 μM. Abstract :